Comparison of Vascular Closure Devices vs Manual Compression After Femoral Artery Puncture in Patients on Oral Anticoagulation - Post Hoc Analysis of the ISAR-CLOSURE Trial - Mayer, Katharina; Gewalt, Senta; Morath, Tanja; Emmer, Christopher; Hilz, Raphaela; Linhardt, Maryam; Hoppe, Katharina; Schmidt, Roland; Bott-Flügel, Lorenz; Laugwitz, Karl Ludwig; Schunkert, Heribert; Kastrati, Adnan; et al. (J INVASIVE CARDIOL, 2021)
OBJECTIVES: To compare vascular closure devices (VCD) with manual compression (MC) in patients on chronic oral anticoagulation (OAC) who undergo diagnostic coronary angiography in terms of vascular access-site complications. METHODS: This is a subanalysis of 604 patients that had undergone transfemoral diagnostic coronary angiography and were randomly assigned to arteriotomy closure with either VCDs (intravascular FemoSeal VCD or extravascular EXOSEAL VCD) or MC within the large scale, randomized ISAR-CLOSURE trial. Primary endpoint was the composite of access-site-related vascular complications at 30 days. Secondary endpoints were time to hemostasis and repeat MC. RESULTS: Vascular access-site complications were similar in patients assigned to VCDs compared to MC (8.2% vs 10.6%; P=.33). There was no interaction of treatment effect and OAC (P interaction = 0.59). Rates of pseudoaneurysms were lower with VCDs (0.8% vs 3.2%; P=.02). Time to hemostasis was significantly shortened with VCDs compared to MC (1 [IQR 0.5-2.0] min vs 12 [IQR 10-15] min; P<.001). There was no difference regarding repeat MC in both groups (VCD 1.5% vs MC 0.5%; P=.23). Time to hemostasis (0.5 [0.2-1.0] min, vs 2.0 [1.75-2.0] min; P<.001) and closure device failure (3.7% vs 17.2%; P<.001) were lower with the intravascular VCD, compared with the extravascular VCD. CONCLUSIONS: In patients on chronic OAC undergoing transfemoral diagnostic coronary angiography, the use of VCDs was comparable to MC regarding the primary combined endpoint of vascular access-site related complications. VCDs reduced the occurrence of pseudoaneurysms and time to hemostasis.
CRIS-Team Scopus Importer:2023-03-08
Keywords: bleeding complications; pseudoaneurysms; vascular closure devices